2013
DOI: 10.1038/cdd.2013.125
|View full text |Cite
|
Sign up to set email alerts
|

The miR-17/92 cluster: a comprehensive update on its genomics, genetics, functions and increasingly important and numerous roles in health and disease

Abstract: The miR-17/92 cluster is among the best-studied microRNA clusters. Interest in the cluster and its members has been increasing steadily and the number of publications has grown exponentially since its discovery with more than 1000 articles published in 2012 alone. Originally found to be involved in tumorigenesis, research work in recent years has uncovered unexpected roles for its members in a wide variety of settings that include normal development, immune diseases, cardiovascular diseases, neurodegenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
706
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 763 publications
(759 citation statements)
references
References 146 publications
23
706
0
13
Order By: Relevance
“…Recent studies have demonstrated an important role for miR-15b-5p (and miR-16-5p that lies in the same genomic cluster), in regulating apoptosis, cell cycle and DNA repair pathways [23], and highlighted miR-15b-5p as a potential target for anti-cancer therapies [24]. Finally, miR-17-5p belongs to one of the most well-studied oncogenic miRNA clusters, miR-17/92, commonly found to be overexpressed in solid tumors including gastric and colorectal cancers [25]. The miR-17/92 cluster family of miRNAs has been shown to target universal cancer genes such as PTEN and E2F which are critical for regulating cell growth and cell death [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated an important role for miR-15b-5p (and miR-16-5p that lies in the same genomic cluster), in regulating apoptosis, cell cycle and DNA repair pathways [23], and highlighted miR-15b-5p as a potential target for anti-cancer therapies [24]. Finally, miR-17-5p belongs to one of the most well-studied oncogenic miRNA clusters, miR-17/92, commonly found to be overexpressed in solid tumors including gastric and colorectal cancers [25]. The miR-17/92 cluster family of miRNAs has been shown to target universal cancer genes such as PTEN and E2F which are critical for regulating cell growth and cell death [25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR-17-5p belongs to one of the most well-studied oncogenic miRNA clusters, miR-17/92, commonly found to be overexpressed in solid tumors including gastric and colorectal cancers [25]. The miR-17/92 cluster family of miRNAs has been shown to target universal cancer genes such as PTEN and E2F which are critical for regulating cell growth and cell death [25]. Altogether, these findings suggest that changes in the expression of tissue miRNAs with biological roles in the malignant degeneration of esophageal tissue may be reflected in the serum exosomes of the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Human Y79 retinoblastoma-derived cells (4 × 10 5 cells per well; ATCC) were transfected with Lipofectamine 2000 (Invitrogen) in 12-well plates with each of the six miRs from the miR-17 family. Distinct time points (3,6,12, and 24 h) as well as various miR concentrations (3, 10, and 30 nM) were tested to evaluate the effects of miR transfection on the levels of HIF1A and VEGFA expression relative to negative controls. Off-target effects and specificity of the selected miRs were further evaluated using the nontargeted, Cy5-labeled control 1 miR (Ambion) at the same time points and concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Members of this family seem to be derived from gene duplication events (9), and despite some divergences in length and nucleotide composition, their seed sequence (AAAGUG) is identical, an attribute suggestive of functional redundancy (10). Although the miR-17-92 cluster has been well-characterized, the regulatory role of the miR-17 family members has not been extensively studied (11,12). Distinct prediction algorithms (13-16) indicate that the miR-17 miR family may target the 3′ UTRs of genes encoding hypoxia-inducible factor-1α (HIF1A) and VEGFA.…”
mentioning
confidence: 99%
“…13,14 Also known as oncomir-1, the cluster enhances cell proliferation or inhibits apoptosis by suppressing targets such as Bim, E2F1 and PTEN and is markedly overexpressed in human cancers. [15][16][17][18][19][20][21] Reduced levels of PHLPP2 in chemoresistant miR-17-92 overexpressing mantle cell lymphomas had suggested that the phosphatase could be a target of oncomir-1. 12 Known major activators of the miR-17-92 cluster are transcription factor c-MYC and members of the E2F family, whereas p53 acts as a repressor under hypoxic conditions.…”
mentioning
confidence: 99%